Bioenhanced Rapid Redox Initiation for RAFT Polymerization in the Air. Issue 19 (30th June 2022) - Yuan, Bolei; Huang, Tingting; Lv, Xiaoxiao; Jiang, Lin; Sun, Xueying; Zhang, Yunhe; Tang, Jun
Abstract: A well‐controlled bioenhanced reversible addition−fragmentation chain transfer (RAFT) in the presence of air is carried out by using glucose oxidase (GOx), glucose, ascorbic acid (Asc acid), and ppm level of hemin. The catalytic concentration of hemin is employed to enhance hydrogen peroxide (H2 O2 )/Asc acid redox initiation, achieving rapid RAFT polymerization. Narrow molecular weight distributions and high monomer conversion ( Ð as low as 1.09 at >95% conversion) are achieved within tens of minutes. Several kinds of monomers are used to verify the universal implication of the presented method. The influences of the pH and feed ratio of each component on the polymerization rate are assessed. Besides, a polymerization rate regulation is realized by managing Asc acid addition. This work significantly increases the rate of redox‐initiated GOx‐deoxygen RAFT polymerization by using simple and green reactants, facilitating the application of RAFT polymerization in areas such as biomedical applications. Abstract : H2 O2 generated by glucose oxidase (GOx) consumption of oxygen reacts with ascorbic acid under the catalysis of hemin to rapidly generate · OH for reversible addition−fragmentation chain‐transfer (RAFT) polymerization initiation in the presence of air.